2015
DOI: 10.2136/sssaj2014.07.0290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aporrectodea Caliginosa on Soil Hydraulic Properties and Solute Dispersivity

Abstract: Earthworms have historically been absent from dryland agricultural fields in eastern Colorado, but their invasion or purposeful introduction may affect water retention and plant nutrient availability in soil. The objective of this study was to determine the effect of Aporrectodea caliginosa on hydraulic properties and solute dispersivity in soil from eastern Colorado (Adena [Ustic Paleargid]–Colby [Aridic Ustorthents] complex) that was amended with biosolids. Columns of repacked soil (50 cm in depth) were incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…A. caliginosa plays several key ecological roles such as nutrient cycling (e.g., increasing nitrogen flux and lowering the C/N ratio (Sandor and Schrader 2007 ; McDaniel et al 2013 ) and enhancing nutrient availability for plants and microorganisms (Sharpley and Syers 1976 ; Sharpley and Syers 1977 ). A. caliginosa can also increase microbial biomass (Svensson and Friberg 2007 ) and its relatively high burrowing activity can have a positive impact on water infiltration /discharge (Ernst et al 2009 ; McDaniel et al 2015 ) and on soil aeration (Francis and Fraser 1998 ). Nevertheless, Eisenia sp .…”
Section: Introductionmentioning
confidence: 99%
“…A. caliginosa plays several key ecological roles such as nutrient cycling (e.g., increasing nitrogen flux and lowering the C/N ratio (Sandor and Schrader 2007 ; McDaniel et al 2013 ) and enhancing nutrient availability for plants and microorganisms (Sharpley and Syers 1976 ; Sharpley and Syers 1977 ). A. caliginosa can also increase microbial biomass (Svensson and Friberg 2007 ) and its relatively high burrowing activity can have a positive impact on water infiltration /discharge (Ernst et al 2009 ; McDaniel et al 2015 ) and on soil aeration (Francis and Fraser 1998 ). Nevertheless, Eisenia sp .…”
Section: Introductionmentioning
confidence: 99%
“…mainly consists of the generation of horizontal burrows at depths ranging between 0 and 10 cm [15]. Endogenic earthworms also create horizontal burrows [52] similar to epigeic ones but at greater depth (between 10 and 30 cm), which also increases the dispersion and retention time of water inside the soil [53,54]. In addition, compared with their surface counterparts, their burrows are usually less connected to the surface, which limits good water infiltration and lessens the hydraulic conductivity in the substrate [13,55].…”
Section: Discussionmentioning
confidence: 99%
“…, showed that the endogeic species A. chlorotica increases the percentage of water-stable aggregates (%WSA) and water holding capacity (WHC) of soil whereas the anecic Lumbricus terrestris only increased %WSA. Of the few other existing studies that consider the impact of earthworms on soil water retention and storage, most report an increase in water retention in the presence of endogeic (mainly A. caliginosa) (Blanchart et al, 1999;McDaniel et al, 2015) and epigeic (Ernst et al 2009;Smagin and Prusak 2008) species or when endogeics are associated with anecic or epigeic species (Boyle et al, 1997;. The effect of endogeics on soil water retention could be due to their burrowing behaviour with greater bioturbation of the soil and aggregate formation resulting in a tortuous and complex burrow system that helps to hold water and ensure more flow into the surrounding soil matrix (Pérès et al, 1998;Weiler and Naef, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the impact of earthworms on soil hydrology will usually be within the context of the presence of plant roots. However, most laboratory-based studies on the impacts of earthworms on soil hydrology are carried out in the absence of plants (Bastardie et al 2003;Capowiez et al 2015;Ernst et al 2009;McDaniel et al 2015). Plant roots penetrate the soil more slowly (at a rate of up to 0.025 m day −1 ) than earthworms (typical burrowing rates of 0.1 to 0.2 m day -1 Ruiz et al 2015).…”
Section: Introductionmentioning
confidence: 99%